2022
DOI: 10.1007/s00261-022-03543-z
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative magnetic resonance imaging can predict prostate cancer with risk for positive surgical margins

Abstract: Purpose Analysis of patients with pre-operative 3 T multiparametric prostate MRI (mpMRI) to determine reliable MRI-based risk predictors of patients at risk for positive surgical margins (PSM) in robotic assisted radical prostatectomy (RPE). Methods Consecutive patients with 3 T mpMRI and subsequent RPE from 01/2015 to 12/2018 were retrospectively included. Patients were compared regarding clinical and MRI related parameters such as length of capsular tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
4
15
1
Order By: Relevance
“…Yao et al demonstrated that preoperative MRI finding was a significant predictor of PSM especially at the prostatic apex 53 . Quentin et al found that the tumor distance to the MU ≤ 3.5 mm was the strongest MRI predictor for PSM at the apical urethra, with showing the highest accuracy of 95% 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al demonstrated that preoperative MRI finding was a significant predictor of PSM especially at the prostatic apex 53 . Quentin et al found that the tumor distance to the MU ≤ 3.5 mm was the strongest MRI predictor for PSM at the apical urethra, with showing the highest accuracy of 95% 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MRI has the ability to predict extracapsular extension and cT stage and is a valid predictor in PC staging [ 25 , 26 ]. For non-metastatic disease in the high-risk group, surgical treatment remains the first option and adjuvant treatment (e.g., radiation therapy or androgen deprivation) might be necessary in some cases, based on the results of RPE histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 179 patients with in-house robotic assisted LRP, M. Quentin et al. found that length of capsular tumor contact was the best MRI predictor for PSMs at the capsule and distance to the membranous urethra for tumors with PSMs at the apical urethra ( 32 ). Irini Youssef et al.…”
Section: Discussionmentioning
confidence: 99%